Influencing medical student choice of primary care worldwide: international application of the four pillars for primary care physician workforce - Weidner, Amanda (Isr J Health Policy Res, 2018)
Primary care is a crucial part of a functional health care system, though in many parts of the world there are current or projected gaps in the primary care physician workforce. The academic family medicine organizations in the United States (US) developed the “Four Pillars for Primary Care Physician Workforce,” a model built on decades of research, highlighting four main areas of emphasis for increasing primary care physician output: 1) pipeline; 2) process of medical education; 3) practice transformation; and 4) payment reform. This commentary proposes that this model, although developed in the US context, is applicable in other medical education settings, including Israel, based on the recently reported findings of Weissman and colleagues in this journal.